À la croisée de l’art et de la science : la cartographie sensible comme dispositif de recherche-création - Élise Olmedo (M@ppemonde)
Through the study of current mapping practices, this article focuses on “subjective maps” as the emergence of a new form of cartography that allows the experience of places to be traced and revealed. By retracing surveys and enquiries with contemporary artists, landscape architects, architects, urban designers engaged in such practices, this article shows how they contextualize their work within a relationship with places and people, thus often expressing an invisible dimension of the areas, an emotional dimension that reveals day to day situations. This contemporary cartography encourages the renewal of science but also, transversally of art and urban design, in that the map is no longer a tool to visualize a place but is itself an apparatus of spatial experience that opens the door to a new geography of how spaces are lived.